All‐Printed Flexible Organic Transistors Enabled by Surface Tension‐Guided Blade Coating. (18th June 2014) - Pierre, Adrien; Sadeghi, Mahsa; Payne, Marcia M.; Facchetti, Antonio; Anthony, John E.; Arias, Ana Claudia
<x xml:space="preserve">Abstract</x> A combination of surface energy‐guided blade coating and inkjet printing is used to fabricate an all‐printed high performance, high yield, and low variability organic thin film transistor (OTFT) array on a plastic substrate. Functional inks and printing processes were optimized to yield self‐assembled homogenous thin films in every layer of the OTFT stack. Specifically, we investigated the effect of capillary number, semiconductor ink composition (small molecule‐polymer ratio), and additive high boiling point solvent concentrations on film fidelity, pattern design, device performance and yields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>